THE REGIME OF BILATERAL INVESTMENT TREATIES BETWEEN GREECE AND NON EU COUNTRIES OF SOUTHERN AND EASTERN EUROPE: THE PERSPECTIVE OF A NECESSARY REFORM - Odysseas SPILIOPOULOS; Athanassia TRIANTAFYLLOPOULOU (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice, 2015)
The Bilateral Investment Treaties (BITs) concluded mainly between developed and developing countries are the main instrument of international investment protection. The EU Member States have concluded with third countries about half of the above agreements which provide, as is well known, primarily for the establishment of standards of treatment of foreign investors and foreign investment in the territory of the host state. Among them, Greece is a contracting party to bilateral agreements of this kind with most countries of Southern and Eastern Europe which are not EU members. These agreements have some key features common to all BITs. The EU member states BITs will gradually be replaced through a long process, by EU Investment Agreements in the framework of the implementation of the new comprehensive EU policy in the field of international investment. The development of this policy is founded on new competences conferred by the Treaty of Lisbon to the EU in this field. Until the aforementioned replacement process is completed, transitional arrangements are in force at EU level. These rules define the conditions according to which the existing member states BITs may continue to apply. Moreover they allow these sates to opt to modify their BITs by setting the conditions under which they may be authorized to do so. In view of this development, the present study attempts to identify and analyze the main negative elements of the main provisions of BITs concluded by Greece, mainly in the 1990s, with third countries of Southeastern Europe. At the same time suggestions to improve these provisions are formulated, so as to achieve the difficult and delicate balance between the protection of foreign investment and the need to ensure the right for regulatory intervention by the host states.